Molecular characterization, expression, and regulation of Gynostemma pentaphyllum squalene epoxidase gene 1 - Guo, Huihong (Plant physiology and biochemistry : PPB, 2016)
Copyright Â© 2016 Elsevier Masson SAS. All rights reserved.